Edukasi dan penyuluhan fisioterapi K3 dalam Meningkatkan Pengetahuan Low Back Pain di Departement Plant PT. Adimitra Baratama Nusantara Sanga Sanga, Kalimantan Timur - Aulia Nahdah Salsabila; Ali Multazam (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Low Back Pain (LBP) is one of the most common musculoskeletal disorders experienced by workers, especially in environments that involve strenuous physical activity, such as in the Plant Department of PT. Adimitra Baratama Nusantara. This condition can interfere with the productivity and quality of life of workers. Therefore, it is important to make prevention and education efforts about LBP. This study aims to measure the effectiveness of Occupational Health and Safety (K3) physiotherapy counseling in improving workers' understanding of LBP and its prevention measures. Counseling was conducted to 25 workers using pre-test and post-test methods to measure the improvement in understanding before and after counseling. The material presented included risk factors, symptoms of LBP, and Williams Flexion Exercise (WFE) exercises as part of prevention. The results showed a significant improvement in workers' understanding of LBP, especially related to the identification of risk factors, symptoms, and prevention techniques. In conclusion, K3 physiotherapy counseling has been shown to be effective in increasing workers' awareness of LBP and providing them with the knowledge to manage it independently.